The Effect of Hedging with Financial Derivatives on Firm Value at Indonesia Stock Exchange - Frensidy, Prof. Dr. Budi (Economics and Finance in Indonesia, 2019)
This study aims to analyze the effect of hedging for the risks of foreign currency, interest rate, and commodity price on firm value as measured by Tobin's Q. The findings reveal that hedging with derivative instruments is insignificantly related to firm value but significantly varied in financial risks. Hedging for foreign currency risk has a significantly positive relation to firm value, while hedging for interest rate and commodity price risk has no relation. Furthermore, this study provides a novelty compared to previous studies in the utilization of the extent of hedging as the variableÂ to measure the implementation of hedging.